Antibiotic resistance in chronic respiratory diseases: from susceptibility testing to the resistome. (25th May 2022) - Pailhoriès, Hélène; Herrmann, Jean-Louis; Velo-Suarez, Lourdes; Lamoureux, Claudie; Beauruelle, Clémence; Burgel, Pierre-Régis; Héry-Arnaud, Geneviève
The development of resistome analysis, i.e. the comprehensive analysis of antibiotic-resistance genes (ARGs), is enabling a better understanding of the mechanisms of antibiotic-resistance emergence. The respiratory microbiome is a dynamic and interactive network of bacteria, with a set of ARGs that could influence the response to antibiotics. Viruses such as bacteriophages, potential carriers of ARGs, may also form part of this respiratory resistome. Chronic respiratory diseases (CRDs) such as cystic fibrosis, severe asthma, chronic obstructive pulmonary disease and bronchiectasis, managed with long-term antibiotic therapies, lead to multidrug resistance. Antibiotic susceptibility testing provides a partial view of the bacterial response to antibiotics in the complex lung environment. Assessing the ARG network would allow personalised, targeted therapeutic strategies and suitable antibiotic stewardship in CRDs, depending on individual resistome and microbiome signatures. This review summarises the influence of pulmonary antibiotic protocols on the respiratory microbiome, detailing the variable consequences according to antibiotic class and duration of treatment. The different resistome-profiling methods are explained to clarify their respective place in antibiotic-resistance analysis in the lungs. Finally, this review details current knowledge on the respiratory resistome related to therapeutic strategies and provides insight into the application of resistome analysis to counter the emergence of multidrug-resistant respiratory pathogens. In chronic respiratory diseases, resistome analysis of respiratory samples provides a more comprehensive understanding of the mechanisms of resistance emergence, constituting a prospective complementary strategy to antibiotic susceptibility testing. https://bit.ly/3vOSPRL